Neural networks for natural language processing - S., Sumathi, 1979-; M., Janani, 1988- (Advances in computer and electrical engineering (ACEE) book series., 2020)
"This book examines natural language processing models and algorithms using traditional symbolic and more recent statistical approaches"--